2023
DOI: 10.3389/fmicb.2023.1224221
|View full text |Cite
|
Sign up to set email alerts
|

REPercussions: how geminiviruses recruit host factors for replication

Sara Shakir,
Muhammad Mubin,
Nazia Nahid
et al.

Abstract: Circular single-stranded DNA viruses of the family Geminiviridae encode replication-associated protein (Rep), which is a multifunctional protein involved in virus DNA replication, transcription of virus genes, and suppression of host defense responses. Geminivirus genomes are replicated through the interaction between virus Rep and several host proteins. The Rep also interacts with itself and the virus replication enhancer protein (REn), which is another essential component of the geminivirus replicase complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 133 publications
0
1
0
Order By: Relevance
“…In geminiviruses, the first difference is that they initiate infection though the different hemipterous insects, which keep the primary target of viruses as differentiated cells. Most viruses cannot replicate in these host insect cells, but Pakkianathan et al reported for the first time that the single-stranded DNA plant virus-like Tomato yellow leaf curl virus (TYLCV) can replicate in its whitefly vector. Whether in plant cells or insect cells, there is a huge challenge of transporting CssDNA into the nucleus.…”
Section: The Cellular Roles Of Cssdnasmentioning
confidence: 99%
“…In geminiviruses, the first difference is that they initiate infection though the different hemipterous insects, which keep the primary target of viruses as differentiated cells. Most viruses cannot replicate in these host insect cells, but Pakkianathan et al reported for the first time that the single-stranded DNA plant virus-like Tomato yellow leaf curl virus (TYLCV) can replicate in its whitefly vector. Whether in plant cells or insect cells, there is a huge challenge of transporting CssDNA into the nucleus.…”
Section: The Cellular Roles Of Cssdnasmentioning
confidence: 99%